2010
DOI: 10.1111/j.1741-3737.2010.00743.x
|View full text |Cite
|
Sign up to set email alerts
|

Educational Progress and Parenting Among Mexican Immigrant Mothers of Young Children

Abstract: This study examined the potential for educational investments in Mexican immigrant mothers to enhance their management of their children’s pathways through an educational system in the U.S. that often disadvantages them. We tested this hypothesis with data on 816 Mexican immigrant women and their children in the Early Childhood Longitudinal Study-Kindergarten Cohort (ECLS-K). The results suggest that mothers who pursued their own schooling over a four year period, regardless of degree attainment, increased the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 44 publications
(50 reference statements)
1
33
0
1
Order By: Relevance
“…Furthermore, when we looked at the number of times they had participated in the Head Start program, we noted that parents reported that they participated in social events an average of six times during the year, whereas they participated in the classroom on a minimum of 14 different occasions, on average. The two subscales were highly correlated ( r = .65), and, thus, similar to the extant literature (e.g., Crosnoe & Kalil, ; Hindman et al, ; Hindman & Morrison, ; McWayne et al, ), we created a latent construct of involvement.…”
Section: Methodsmentioning
confidence: 62%
“…Furthermore, when we looked at the number of times they had participated in the Head Start program, we noted that parents reported that they participated in social events an average of six times during the year, whereas they participated in the classroom on a minimum of 14 different occasions, on average. The two subscales were highly correlated ( r = .65), and, thus, similar to the extant literature (e.g., Crosnoe & Kalil, ; Hindman et al, ; Hindman & Morrison, ; McWayne et al, ), we created a latent construct of involvement.…”
Section: Methodsmentioning
confidence: 62%
“…In the case of Mexican immigrant parents, for example, maternal education was seen to have provided an important basis of parents' expectations for children's academic achievements. Mexican immigrant parents who did not pursue their own high schooling did not have a strong motivation for their children's academic success (Corsnoe & Kalil, 2010). According to Urdan and Munoz (2012), generally speaking, "the academic motivation of the children of immigrant parents depends on a number of factors, [including] the educational and income level of parents, attitudes of the host society and institutions like school toward the immigrant group" (p. 249).…”
Section: Discussionmentioning
confidence: 99%
“…These resources can take may different forms, such as parents’ own educational histories and their English language proficiency. For example, parents own educational attainment plays an integral role in shaping their investments in their children both in terms of time investments, such as engagement in different types of cognitively stimulating activities (Crosnoe & Kalil, 2010), as well as monetary investments, such as preschool enrollment (Fuller et al, 1996). There has also been growing collaboration between various state-, city-, and neighborhood-level agencies and local preschool programs as one means of increasing parents’ awareness of preschool education.…”
Section: The Accommodations Model For Preschool Selectionmentioning
confidence: 99%